Institutional Responses to Inclusion from Around the World - Trendl, Fanni (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Book: Jaimie Hoffman, Patrick Blessinger and Mandla Makhanya (Eds). (2019). Strategies for Facilitating Inclusive Campuses in Higher Education. International Perspectives on Equity and Inclusion. Innovations in Higher Education Teaching and Learning. Volume 17. Emerald Publishing Limited. Howard House, UK. p. 309.